Early determinants of blood pressure among adults of the 1982 birth cohort, Pelotas, Southern Brazil - Horta, Bernardo L (2008)
OBJECTIVE: To evaluate the effects of exposure occurring during pregnancy or the first years of life on blood pressure. METHODS: Cohort study on all children born in 1982 in maternity hospitals in the city of Pelotas, Southern Brazil. The mothers living in the urban area were interviewed and the children were followed up on different occasions. In 2004-5, all the individuals in the cohort were sought for monitoring. Their blood pressure was measured twice, at the start and end of the interview, using a digital wrist sphygmomanometer. Associations between blood pressure and the following variables were evaluated: skin color; maternal schooling level; family income at birth; change in income between birth and 23 years of age; birth weight; and duration of breastfeeding. Analysis of variance was used to compare the means and a generalized linear model was used in the adjusted analysis. RESULTS: Blood pressure measurements were obtained from 4,291 individuals: 2,208 males and 2,083 females. The mean systolic blood pressure was 117.5 ± 15.0 mmHg and the mean diastolic was 73.6 ± 11.5 mmHg. Among the men, systolic blood pressure was higher among those of black or brown skin color and among those who were never considered poor. Diastolic pressure was only associated with birth weight. Among the women, systolic blood pressure was greater among those of black or brown skin color whose mothers' schooling level was greater than or equal to 12 years or whose birth weight was less than 4,000 g. CONCLUSIONS: For both sexes, only skin color was associated with blood pressure. Breastfeeding did not have any long-term effect on blood pressure and the associations for birth weight and socioeconomic level were inconsistent.